Managing Behavioural Outcomes of Repatriates through a Proactive Model - Jayasekara, Padmini (Archives of Business Research, 2020)
This study attempts to present a proactive model in explaining a mechanism which ensures behavioral outcomes of repatriates. A series of activities, which were already well researched in an isolated manner in different contexts were incorporated to develop this model. The literature based data compilation was done to develop this model. The key of pre-departure stage of expatriation, on-assignment stage of expatriation, post- assignment period of expatriation, expatriate adjustment, repatriate adjustment, behavioural outcomes of repatriates, social support for expatriates, social support for repatriates, organizational support for expatriate families, organizational support for repatriate families, and cross-over effect of expatriate adjustment were included to the Google Scholar search engine to find the articles.This model outlines logic on the necessity of being proactive on returnees’ post-assignment behavioural outcomes, by taking into account three time stages of pre-departure, on-assignment, and post assignment stages.